1986
DOI: 10.1111/j.1532-5415.1986.tb06332.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use By Ambulatory Elderly

Abstract: The elderly residents of an urban subsidized apartment building were interviewed in their apartments to determine a comprehensive medication profile. The interviews were conducted by doctor of pharmacy candidates, and 155 residents (81.2%) participated. Compliance was similar to rates previously reported (49.3%), and adverse drug reactions were common (29.1%). Other findings included: compliance did not decrease with advancing age; most elderly individuals could open child-resistant containers (83.4%), read st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 16 publications
1
34
0
1
Order By: Relevance
“…More specifically, nonadherence to pharmacotherapy has been associated with such variables as daily dosing frequencies [24••,28,29, 49-51], the number of concurrent medications [22,29,52], and therapeutic turbulence, including such changes as switches, additions, or removal of medication [25••,52].…”
Section: Regimen Complexitymentioning
confidence: 99%
“…More specifically, nonadherence to pharmacotherapy has been associated with such variables as daily dosing frequencies [24••,28,29, 49-51], the number of concurrent medications [22,29,52], and therapeutic turbulence, including such changes as switches, additions, or removal of medication [25••,52].…”
Section: Regimen Complexitymentioning
confidence: 99%
“…While the elderly comprise just 12 percent of the total population, they consume 31 percent of all prescription medications.2 It is common for elders to be taking multiple medications simultaneously. [3][4][5][6] Many have underlying heart, liver, kidney, or lung diseases, any ofwhich might complicate an overdose situation or affect the pharmacokinetics of a drug or toxin.7-9 Also, 2-4 million older Americans suffer from dementia'0; such patients may be confused and have difficulty complying with complicated dosage regimens. Failing eyesight and memory may be responsible for medication errors or for mistaking household products as potables.…”
Section: Discussionmentioning
confidence: 99%
“…Their use of NSAlDs is more than 3.5 times greater than their younger counterparts (4). Our own survey of elderly persons living in urban public housing complexes revealed that NSAlDs were the most frequently used OTC and prescription drugs (11). Worldwide statistics from 1987 regarding NSAID use and sales of NSAlDs (including the USA) revealed that three of the top 10 most-used drugs were NSAlDs and that their sales had increased 21% from 1986 to 1987 (12).…”
Section: Introductionmentioning
confidence: 97%